Atomic Layer Deposition of Hafnium(IV) Oxide on Graphene Oxide: Probing Interfacial Chemistry and Nucleation by using X‐ray Absorption and Photoelectron Spectroscopies. Issue 13 (27th July 2015) - Alivio, Theodore E. G.; De Jesus, Luis R.; Dennis, Robert V.; Jia, Ye; Jaye, Cherno; Fischer, Daniel A.; Singisetti, Uttam; Banerjee, Sarbajit
Abstract Interfacing graphene with metal oxides is of considerable technological importance for modulating carrier density through electrostatic gating as well as for the design of earth‐abundant electrocatalysts. Herein, we probe the early stages of the atomic layer deposition (ALD) of HfO2 on graphene oxide using a combination of C and O K‐edge near‐edge X‐ray absorption fine structure spectroscopies and X‐ray photoelectron spectroscopy. Dosing with water is observed to promote defunctionalization of graphene oxide as a result of the reaction between water and hydroxyl/epoxide species, which yields carbonyl groups that further react with migratory epoxide species to release CO2. The carboxylates formed by the reaction of carbonyl and epoxide species facilitate binding of Hf precursors to graphene oxide surfaces. The ALD process is accompanied by recovery of the π‐conjugated framework of graphene. The delineation of binding modes provides a means to rationally assemble 2D heterostructures.